2007
DOI: 10.1097/bot.0b013e3180caa138
|View full text |Cite
|
Sign up to set email alerts
|

The Severity and Prediction of Anterior Knee Pain Post Tibial Nail Insertion

Abstract: There is a significant preinjury prevalence of anterior knee pain. Postnailing knee pain severity correlates with that in the uninjured limb. Relative risk of anterior knee pain postnailing is twice that of a comparative population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
0
18
0
3
Order By: Relevance
“…Multiple studies with small cohorts have reported on knee pain associated with tibia fractures with incidence and severity ranging greatly. 1,3-6, 8, 15-18-25 Court-Brown et al followed one of the largest series of 169 patients and found a 56% incidence of knee pain 1 . However, the study included mild pain in the total percent of patients with pain.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies with small cohorts have reported on knee pain associated with tibia fractures with incidence and severity ranging greatly. 1,3-6, 8, 15-18-25 Court-Brown et al followed one of the largest series of 169 patients and found a 56% incidence of knee pain 1 . However, the study included mild pain in the total percent of patients with pain.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important unresolved question that requires a different study design to address. Related to this, many survey studies in orthopaedic surgery evaluate the effects of major surgical interventions [2,5,10,15,17,23,26,27,33]; ours evaluated a mixed cohort of patients, many of whom had minor interventions or no intervention apart from the office visit. It is difficult to estimate what influence this difference might introduce on our results.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors like damage to articular surface and meniscus, injury to the infrapatellar branch of the saphenous nerve, infrapatellar fat pad, nail prominence, thigh muscle weakness, and small plateau width contribute to the pain 4,11 . Incidence of anterior knee pain has been noted between 31% to 86% in various studies [13][14][15][16][17][18][19][20] . Fourty-two patients (41%) developed anterior knee pain in this study which is comparable to other similar studies.…”
Section: Discussion:-mentioning
confidence: 99%